Determinants of Profit Sharing in the Finnish Corporate Sector - Laura Arranz-Aperte; Almas Heshmati (Institute for the Study of Labor (IZA), 2003)
This study investigates the role of factors that determine individual employees? and firms? participation in profit sharing schemes. Using a large panel data of Finnish employees for the period 1996-2000 we analyse individual and workplace characteristics that make firms employ profit sharing schemes and workers susceptible of receiving profit sharing bonuses. In particular two links between profit sharing schemes and workers performance have been analysed. First, in looking at profit sharing as an incentive device the results show a positive link between firm size and monitoring costs. Second, we find that younger individuals with higher mean salary and capacity to bear risk are more susceptible to profit sharing schemes. The industrial sector in which the individual is employed is also an important determinant factor.
Keywords: J41; E24; C23; J30; 330; individual; firm; profit sharing; panel data; Tarifliche Gewinnbeteiligung; Erfolgsbeteiligung; Leistungsanreiz; Humankapital; Risikopräferenz; Lebensalter; Branche; Betriebsgröße; Schätzung; Finnland